Evaluation of a university seminar on the use of digital media in the physics classroom - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Journal of Physics: Conference Series)
Abstract Fostering digital competencies is an important aspect of pre-service teacher education. However, for physics, there is a lack of systematically surveyed and evidence-based seminars that specifically take into account relevant research findings. Thus, we developed a research-based seminar on the effective use of digital media in physics classrooms and investigated its effects on pre-service teachers (PSTs) professional competencies in a mixed-methods design. Our quantitative analyses of different competence components surveyed in a pre-post-design indicate that the seminar leads to an increase in motivation to use digital media in the physics classroom. Nevertheless, no significant increase in digital-media PCK was found, which could be due to the small sample. The seminar design, however, was predominantly evaluated positively by experts and PSTs in guided interviews. Based on the results, it is planned to further refine the original seminar using a Design-Based Research approach.

An eye-tracking study on pre-service teachers' professional vision in class. Poster Presentation. EARLI SIG 15 Biennial Conference 2024 ‘Special Educational Needs’. “Neurodiversity in Education: Research and Practice”. - Görel, Gamze; Finke, Pauline; Hellmich, Frank

DFT‐Assisted Investigation of the Electric Field and Charge Density Distribution of Pristine and Defective 2D WSe2 by Differential Phase Contrast Imaging - Groll, Maja; Bürger, Julius; Caltzidis, Ioannis; Jöns, Klaus D.; Schmidt, Wolf Gero; Gerstmann, Uwe; Lindner, Jörg K. N. (Small)
Abstract Most properties of solid materials are defined by their internal electric field and charge density distributions which so far are difficult to measure with high spatial resolution. Especially for 2D materials, the atomic electric fields influence the optoelectronic properties. In this study, the atomic‐scale electric field and charge density distribution of WSe 2 bi‐ and trilayers are revealed using an emerging microscopy technique, differential phase contrast (DPC) imaging in scanning transmission electron microscopy (STEM). For pristine material, a higher positive charge density located at the selenium atomic columns compared to the tungsten atomic columns is obtained and tentatively explained by a coherent scattering effect. Furthermore, the change in the electric field distribution induced by a missing selenium atomic column is investigated. A characteristic electric field distribution in the vicinity of the defect with locally reduced magnitudes compared to the pristine lattice is observed. This effect is accompanied by a considerable inward relaxation of the surrounding lattice, which according to first principles DFT calculation is fully compatible with a missing column of Se atoms. This shows that DPC imaging, as an electric field sensitive technique, provides additional and remarkable information to the otherwise only structural analysis obtained with conventional STEM imaging.

Randomised material parameter impedance dataset of piezoelectric rings - Koch, Kevin; Friesen, Olga; Claes, Leander

Randomised material parameter piezoelectric impedance dataset with structured electrodes - Koch, Kevin; Claes, Leander

Compact, High-Speed Mach-Zehnder Modulator with On-Chip Linear Drivers in Photonic BiCMOS Technology - Kress, Christian; Schwabe, Tobias; Rhee, Hanjo; Scheytt, J. Christoph (IEEE Access)

Evaluation of a university seminar on the use of digital media in the physics classroom - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Journal of Physics: Conference Series)
Abstract Fostering digital competencies is an important aspect of pre-service teacher education. However, for physics, there is a lack of systematically surveyed and evidence-based seminars that specifically take into account relevant research findings. Thus, we developed a research-based seminar on the effective use of digital media in physics classrooms and investigated its effects on pre-service teachers (PSTs) professional competencies in a mixed-methods design. Our quantitative analyses of different competence components surveyed in a pre-post-design indicate that the seminar leads to an increase in motivation to use digital media in the physics classroom. Nevertheless, no significant increase in digital-media PCK was found, which could be due to the small sample. The seminar design, however, was predominantly evaluated positively by experts and PSTs in guided interviews. Based on the results, it is planned to further refine the original seminar using a Design-Based Research approach.

Enabling Performance Portability for Shallow Water Equations on CPUs, GPUs, and FPGAs with SYCL - Büttner, Markus; Alt, Christoph; Kenter, Tobias; Köstler, Harald; Plessl, Christian; Aizinger, Vadym (Proceedings of the Platform for Advanced Scientific Computing Conference (PASC))

State of Knowledge Managementamong German firefighters - Schultz, Andreas Maximilian; Dotzki, Fabian; Mozgova, Iryna (Proceedings of the 21st ISCRAM Conference)

Mediale Erinnerungskonfigurationen – Lea Streisands Romane "Der Lappen muss hoch" und "Im Sommer wieder Fahrrad" - Willeke, Stephanie ('Topographisches' Schreiben: Lea Streisand)

Mathematikleistungen von Grundschulkindern im Zusammenhang mit dem von ihnen wahrgenommenen Feedback und ihrer Motivation im Mathematikunterricht. Vortrag auf der 11. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung verstehen – Partizipation erreichen – Transfer gestalten“ - Finke, Nils; Hellmich, Frank

"I'm actually going to go and change these passwords": Analyzing the Usability of Credential Audit Interfaces in Password Managers - Kablo, Emiram; Kader, Katharina; Arias Cabarcos, Patricia (Extended Abstracts of the CHI Conference on Human Factors in Computing Systems)

Realization of high-fidelity unitary operations on up to 64 frequency bins - De, Syamsundar; Ansari, Vahid; Sperling, Jan; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physical Review Research)
The ability to apply user-chosen large-scale unitary operations with high fidelity to a quantum state is key to realizing future photonic quantum technologies. Here, we realize the implementation of programmable unitary operations on up to 64 frequency-bin modes. To benchmark the performance of our system, we probe different quantum walk unitary operations, in particular, Grover walks on four-dimensional hypercubes with similarities exceeding 95% and quantum walks with 400 steps on circles and finite lines with similarities of 98%. Our results open a path toward implementing high-quality unitary operations, which can form the basis for applications in complex tasks, such as Gaussian boson sampling. Published by the American Physical Society 2024

The conditional impact of market consolidation and market power on banking stability – Evidence from Europe - Herwald, Sarah; Voigt, Simone; Uhde, André (Journal of Risk Finance)
Purpose Academic research has intensively analyzed the relationship between market concentration or market power and banking stability but provides ambiguous results, which are summarized under the concentration-stability/fragility view. We provide empirical evidence that the mixed results are due to the difficulty of identifying reliable variables to measure concentration and market power. Design/methodology/approach Using data from 3,943 banks operating in the European Union (EU)-15 between 2013 and 2020, we employ linear regression models on panel data. Banking market concentration is measured by the Herfindahl–Hirschman Index (HHI), and market power is estimated by the product-specific Lerner Indices for the loan and deposit market, respectively. Findings Our analysis reveals a significantly stability-decreasing impact of market concentration (HHI) and a significantly stability-increasing effect of market power (Lerner Indices). In addition, we provide evidence for a weak (or even absent) empirical relationship between the (non)structural measures, challenging the validity of the structure-conduct-performance (SCP) paradigm. Our baseline findings remain robust, especially when controlling for a likely reverse causality. Originality/value Our results suggest that the HHI may reflect other factors beyond market power that influence banking stability. Thus, banking supervisors and competition authorities should investigate market concentration and market power simultaneously while considering their joint impact on banking stability.
Keywords: market concentration; market power; banking stability; European banking

Uniaxial and biaxial experimental investigation of glassy polymers - Hamdoun, Ayoub; Mahnken, Rolf (Polymer)

A large deformation gradient theory for glassy polymers by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (Archive of Applied Mechanics)
Abstract Cold forming of polycarbonate films results in the formation of shear bands in the necking zone. The numerical results obtained from standard viscoplastic material models exhibit mesh size dependency, requiring mathematical regularization. For this purpose, we present in this work a large deformation gradient theory for a viscoplastic isotropic material model published before. We extend our model to a micromorphic model by introducing a new micromorphic variable as an additional degree of freedom along with its first gradient. This variable represents a microequivalent plastic strain. The relation between the macroequivalent plastic strain and the micromorphic variable is accomplished by a micromorphic coupling modulus. This coupling forces proximity between the macro- and microvariables, leading to the targeted regularization effect. The micromorphic model is implemented as a three-dimensional initial boundary value problem in an in-house finite element tool. The analysis is performed for both uniaxial and biaxial specimens. The provided numerical examples show the ability of our model to regularize shear bands within the specimens and address the issue of localization.

Digitale Plattformen im industriellen Mittelstand

Kraft, Kerstin und Regina Lösel: Forscherinnen und Kleidung in Bewegung. - Kraft, Kerstin

Towards New Realities: Implications of Personalized Online Layers in Our Daily Lives - Herder, Eelco; Stojko, Laura; Strecker, Jannis; Neumayr, Thomas; Yigitbas, Enes; Augstein, Mirjam (i-com - Journal of Interactive Media, Special Issue on “The Future of Human-Computer Interaction” (to appear))

Von Transzendenz zum Transhumanismus. Deutungskulturen von (Un-)Heilsgeschichte im 19. und 20. Jahrhundert

Weihnachts-Werbespots als moderne Krippenspiele

Gebete im Islamischen Religionsunterricht - Candan, Ayse Beyza (Zum Gebet einladen. Impulse aus der Praxis des evangelischen, islamischen und katholischen Religionsunterrichts.)

Exploring Custom FPGA Accelerators for DNN-based RF Fingerprinting - Henke, Luca-Sebastian

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gilich, Julian; Meschut, Gerson; Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik (14. Doktorandenseminar Klebtechnik)

Further information about neural valence-dependent processing of augmented feedback in extensive motor practice: An analysis of frontal theta-band activity - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Pappert, Steffen/Roth, Kersten Sven (Hg.) (2023): Zeitlichkeit in der Textkommunikation. - Markewitz, Friedrich (Zeitschrift für Medienlinguistik)

Religion und Freiheit - Süßmann, Johannes

§ 16 a (Girokonto und Zahlungsdiensterahmenvertrag) - Bartlitz, David (Verbraucherrecht)

Gesetz über digitale Märkte (Digital Markets Act) - Bartlitz, David; Gräfe, Alexander (Handbuch des EU-Wirtschaftsrechts)

§ 78 (Kartellrechtliche Grenzen der stillen Gesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

§ 6 (Kartellrechtliche Grenzen der Kommanditgesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

Digital Dotted Lines: Design and Evaluation of a Prototype for Digitally Signing Documents Using Identity Wallets - Last, Yorick; Geels, Jorrit; Schraffenberger, Hanna (Extended Abstracts of the CHI Conference on Human Factors in Computing Systems (CHI EA ’24))
Documents are largely stored and shared digitally. Yet, digital documents are still commonly signed using (copies of) handwritten signatures, which are sensitive to fraud. Though secure, cryptography-based signature solutions exist, they are hardly used due to usability issues. This paper proposes to use digital identity wallets for securely and intuitively signing digital documents with verified personal data. Using expert feedback, we implemented this vision in an interactive prototype. The prototype was assessed in a moderated usability test (𝑁 = 15) and a subsequent unmoderated remote usability test (𝑁 = 99). While participants generally expressed satisfaction with the system, they also misunderstood how to interpret the signature information displayed by the prototype. Specifically, signed documents were also trusted when the document was signed with irrelevant personal data of the signer. We conclude that such unwarranted trust forms a threat to usable digital signatures and requires attention by the usable security community.

Einführung in das Bürgerliche Recht

Data Envelopment Analysis: From Non-Monotonic to Monotonic Scale Elasticities - Dellnitz, A.; Tavana, Madjid (European Journal of Operational Research)

A Novel Fuzzy General Best-Worst Method for Considering Diversity and Inclusion in Supplier Selection Programs - Tavana, Madjid; Sorooshian, S.; Sarvarizadehkouhpaye, M.; Mina, H. (Annals of Operations Research)

A Two-Level Supply Chain Coordination Model for Perishable Products under Optimal Markdown Time and Trade Credit Policies - Setak, M.; Tavana, Madjid; Talafi Daryani, H. (OPSEARCH)

On the Capacity of Artificial Intelligence Techniques and Statistical Methods to Deal with Low Quality Data in Medical Supply Chain Environments - Santos-Arteaga, F.J.; Di Caprio, D.; Tavana, Madjid; Cucchiari, D.; Campistol, J.M.; Oppenheimer, F.; Diekmann, F.; Revuelta, I. (Engineering Applications of Artificial Intelligence)

A Full Ranking Method in Data Envelopment Analysis with Multi-Criteria Decision Analysis - Tavana, Madjid; Bonyani, A.; Karimi, T. (International Journal of Applied Management Science)

Jahrgangsteams zur Kooperation mit Eltern anregen – eine Aufgabe für Fortbildungen? Evaluationsergebnisse zum Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) - Grüter, Sandra; Gorges, Julia; Lütje-Klose, Birgit; Neumann, Phillip; Wild, Elke (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Für eine gelingende Umsetzung schulischer Inklusion gilt eine professionelle Weiterbildung der Lehrkräfte und des weiteren Schulpersonals als unverzichtbare Voraussetzung, um eine effektive Teamarbeit sowie die Einbindung von Eltern [i] in Erziehungs- und Bildungsprozesse zu gewährleisten. Im Projekt BiFoKi [ii] (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde eine Fortbildungsmaßnahme für inklusive Schulen entwickelt, die sowohl die intrainstitutionelle Kooperation innerhalb der Schule als auch die interinstitutionelle Zusammenarbeit mit den Eltern der Schüler*innen mit und ohne sonderpädagogischen Unterstützungsbedarf adressiert. Die Fortbildung zielt u.a. darauf ab, durch eine im Jahrgangsteam gemeinsam geplante und verantwortete Elternarbeit eine einladende Atmosphäre zu schaffen, Kommunikationswege an diverser werdende Bedarfe der Eltern und der Schüler*innen anzupassen und Eltern stärker in schulische Bildungsprozesse einzubeziehen. Zur Evaluation der Fortbildung wurde eine quasi-experimentelle Studie mit einem Prä-Post-Kontrollgruppendesign realisiert. Längsschnittliche Daten liegen für 55 Lehr- und Fachkräfte vor. Die Ergebnisse der varianzanalytischen Auswertung zeigen, dass sich die Einschätzungen zur Kooperationsbereitschaft der Eltern sowie das selbstberichtete Kooperationsverhalten im Bereich der Erziehungs- und Bildungskooperation in der Interventionsgruppe nach der Teilnahme an der Fortbildung signifikant positiver entwickelt hat als in der Kontrollgruppe. [i] Mit dem Begriff Eltern sind hier alle erziehungs- bzw. sorgeberechtigten Personen gemeint. [ii] Hinweis zur Finanzierung: Das diesem Beitrag zugrunde liegende Vorhaben BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde mit Mitteln des Bundesministeriums für Bildung und Forschung unter dem Förderkennzeichen 01NV1732in der Förderlinie „Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung“ gefördert (Projektleitung: Birgit Lütje-Klose, Elke Wild, Julia Gorges und Phillip Neumann).
Keywords: Inklusion; Kooperation; Eltern; Sekundarstufe 1; Evaluation; Integration; Schulentwicklung; Elternkooperation

The meaning landscape of the concept of the total derivative in multivariable real analysis textbooks: an analysis based on a new model of meaning - Lankeit, Elisa; Biehler, Rolf (ZDM – Mathematics Education)
Abstract In this paper, we propose a novel conceptual framework tailored for modeling the meaning of mathematical concepts in university-level mathematics, addressing their rigorous nature and their relationships with related concepts as well as interpretations in various contexts. Within this framework, we present a model of meaning for the concepts of total differentiability and total derivative that provides a variety of possible interpretations and aspects. We then use the proposed model of meaning as a tool for analyzing three different textbooks for mathematics majors on the topic of multidimensional differentiability. ﻿Our paper is an example of a subject matter analysis of a topic in university mathematics carried out in a structured way. The model of meaning for total differentiability presented in this paper could inspire course design and analysis including the design of assignments and assessments for students. Moreover, it could serve as a valuable research tool for further analyses. For example, it could be used as a framework for analyzing courses taught or as a basis for developing a test instrument to assess students’ understanding. With our textbook analysis, we begin to examine the landscape of textbooks regarding differentiability concepts in the multidimensional case, shedding light on the diversity of meaning facets that are covered in the textbooks. These results could be useful for guiding instructors and learners in selecting and using textbooks for teaching and learning based on their respective needs.

Method development (modelling, simulation, characterisation) in adhesive bonding technology - Beule, Felix; Al Trjman, Mohamad; Teutenberg, Dominik; Meschut, Gerson

Reliable electrocortical dynamics of target-directed pass-kicks - Piskin, Daghan Yuksel; Büchel, Daniel; Lehmann, Tim; Baumeister, Jochen (Cognitive Neurodynamics)
Abstract Football is one of the most played sports in the world and kicking with adequate accuracy increases the likelihood of winning a competition. Although studies with different target-directed movements underline the role of distinctive cortical activity on superior accuracy, little is known about cortical dynamics associated with kicking. Mobile electroencephalography is a popular tool to investigate cortical modulations during movement, however, inherent and artefact-related pitfalls may obscure the reliability of functional sources and their activity. The purpose of this study was therefore to describe consistent cortical dynamics underlying target-directed pass-kicks based on test–retest reliability estimates. Eleven participants performed a target-directed kicking task at two different sessions within one week. Electroencephalography was recorded using a 65-channel mobile system and behavioural data were collected including motion range, acceleration and accuracy performance. Functional sources were identified using independent component analysis and clustered in two steps with the components of first and subsequently both sessions. Reliability estimates of event-related spectral perturbations were computed pixel-wise for participants contributing with components of both sessions. The parieto-occipital and frontal clusters were reproducible for the same majority of the sample at both sessions. Their activity showed consistent alpha desyhronization and theta sychnronisation patterns with substantial reliability estimates revealing visual and attentional demands in different phases of kicking. The findings of our study reveal prominent cortical demands during the execution of a target-directed kick which may be considered in practical implementations and provide promising academic prospects in the comprehension and investigation of cortical activity associated with target-directed movements.
Keywords: Exercise Neuroscience

Was ist literaturwissenschaftliche Ideengeschichte? (Scientia Poetica)

Ideengeschichte als Zeitschriftenforschung - Heise, Tillmann (Scientia Poetica)

Umkämpfte Semantiken des ‚Europäischen‘ in der Weltanschauungsliteratur der Zwischenkriegszeit - Heise, Tillmann (Forum Interdisziplinäre Begriffsgeschichte)

Unbreakable and breakable quantum censorship - Pinske, Julien; Sperling, Jan (Physical Review A)

Das ‚andere‘ Europa der Schriftsteller. Ideen, Netzwerke und Schreibweisen des antiliberalen Europa-Diskurses in Deutschland und Österreich (1918–1934) - Heise, Tillmann

"Der Zeitgeist" (1922/23). Expressionismus in Österreich zwischen Kunst- und Weltanschauung - Heise, Tillmann (Expressionismus)

Efficient Evaluation of Conjunctive Regular Path Queries Using Multi-way Joins - Karalis, Nikolaos; Bigerl, Alexander; Heidrich, Liss; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (ESWC)
Keywords: bigerl dice enexa heidrich karalis ngonga sail sherif

Fachbezogene Professionalisierung von fachfremd Mathematik unterrichtenden Lehrkräften: Retrospektive Selbsteinschätzungen zur Expertise im Umgang mit Schwierigkeiten beim Mathematiklernen im Anfangsunterricht der Grundschule - Häsel-Weide, Uta; Graf, Lara Marie; Höveler, K.; Nührenbörger, M. (HLZ – Herausforderung Lehrer*innenbildung)

Ironie - Markewitz, Friedrich
Ironie lässt sich als uneigentliches Kommunikationsmittel beschreiben, mit dem etwas anderes zum Ausdruck gebracht wird, als Sprecher*innen oder Schreiber*innen eigentlich meinen. Dies erfordert eine Differenzierung in Gesagtes und Gemeintes. Doch diese Differenzierung ist längst nicht immer eindeutig und so lebt Ironie von einer interpretatorischen Ambivalenz, ob eine Äußerung wörtlich oder ironisch zu verstehen ist. Aufgrund dieser Ambivalenz und ihrer kulturgeschichtlichen Entwicklung erscheint Ironie als ebenso faszinierendes wie komplexes Sprach-Phänomen. Die vorliegende Einführung gibt aus kulturlinguistischer Perspektive Einblicke in die verschiedenen Möglichkeiten der theoretischen Beschreibung, methodischen Erfassung sowie empirischen Analyse von Ironie. Dabei werden einerseits alltagssprachliche Formen ironischen Kommunizierens in den Blick genommen, andererseits Möglichkeiten des interdisziplinären Anschlusses, um Ironie als linguistisches sowie als kulturgeschichtliches Phänomen zugänglich zu machen.

Orte und Erinnerung. Eine Kartografie des Israelkorpus - Markewitz, Friedrich (Zeitschrift für Angewandte Linguistik)

“Der Draht ist gut, hält uns ab vom dummen Leben“. Ironisierung als kommunikativer Versuch des Umgangs mit Entwertungs- und Gewalterfahrungen durch jüdische Textproduzenten im Getto Litzmannstadt - Markewitz, Friedrich (Invective Discourse)
Immediately after the National Socialist seizure of power, a comprehen-sive social, legal and ultimately existential exclusion of Jewish people began. The disturbing perception of the break-up of previous understandings of the world was intensified against the background of the acts of annihilation by the National Socialists. Countering this in a communicative form became an often agonizing challenge for Jewish speakers, but also a necessary need. This paper will focus on a communicative phenomenon that has been little researched in linguistics so far: The use of irony to counter experiences of devaluation and violence. By eval-uating ironic utterances in textual communications of the Litzmannstadt ghetto, the criticism of elements of National Socialist ideology will be tentatively made understandable, as well as the experiences of violence within the ghetto.

Haus oder Schule? oder Haus und Schule? Zur kulturell-gesellschaftlichen Bedeutung der historischen Textsorte 'Schulprogramm' hinsichtlich der Konstitution, Festigung wie Abgrenzung des Erziehungssystems im 19. Jahrhundert - Markewitz, Friedrich (Textsorten in Sprach-, Kultur- und Sozialgeschichte)

On the global impact of Erich Mendelsohn’s architecture. Sergio Larraín’s Oberpaur building in Santiago and the beginnings of modernist architecture in Chile - Silvestri, Marco (Positioning: Erich Mendelsohn and the Built Heritage of the 20th Century)

Measuring Visual Attention Capacity Across xReality - Biermeier, Kai; Scharlau, Ingrid; Yigitbas, Enes (Proceedings of the 17th International Conference on PErvasive Technologies Related to Assistive Environments (PETRA 2024))

The Imperative of Revival Strategies through Digital Transformation in the Cultural Sector - A Taxonomy Approach - Althaus, Maike; Hansmeier, Philipp (Proceedings of the ECIS 2024)

Quasimodogeniti (07.04.2024) Joh 20,19-20(21-23)24-29: Vom Safe Space zum Escape Room: Der gläubige Thomas - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Seven Psalms. Paul Simons theologische Kammermusik - Schroeter-Wittke, Harald (Praktische Theologie)

Homiletischer "freejazz". Des Gerechten Gebet vermag viel. Eine Partytour - Schroeter-Wittke, Harald; Scheidegger, Martin (Pastoraltheoogie)

Pop-Ikonen. Transformationen des Heiligen in der deutschen Pop(musik)kultur. - Jacke, Christoph; Schroeter-Wittke, Harald ((Un)verfügbar. Kulturen des Heiligen.)

Street Signs, New York (2018). - Autsch, Sabiene (Festschrift für Thomas Krettenauer)

Polyhedral bounds on the joint spectrum and temperedness of locally symmetric spaces - Lutsko, Christopher; Weich, Tobias; Wolf, Lasse Lennart (arXiv:2402.02530)
Given a real semisimple connected Lie group $G$ and a discrete torsion-free subgroup $Γ < G$ we prove a precise connection between growth rates of the group $Γ$, polyhedral bounds on the joint spectrum of the ring of invariant differential operators, and the decay of matrix coefficients. In particular, this allows us to completely characterize temperedness of $L^2(Γ\backslash G)$ in this general setting.

Temperedness of locally symmetric spaces: The product case - Weich, Tobias; Wolf, Lasse Lennart (Geom Dedicata)
Let $X=X_1× X_2$ be a product of two rank one symmetric spaces of non-compact type and $Γ$ a torsion-free discrete subgroup in $G_1× G_2$. We show that the spectrum of $Γ \backslash X$ is related to the asymptotic growth of $Γ$ in the two direction defined by the two factors. We obtain that $L^2(Γ \backslash G)$ is tempered for large class of $Γ$.

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Detection and Characterization of Hydride Ligands in Copper Complexes by Hard X‐ray Spectroscopy - Fritsch, Lorena; Rehsies, Pia; Barakat, Wael; Estes, Deven P.; Bauer, Matthias (Chemistry – A European Journal)
Transition metal complexes, particularly copper hydrides, play an important role in various catalytic processes and molecular inorganic chemistry. This study employs synchrotron hard X‐ray spectroscopy to gain insights into the geometric and electronic properties of copper hydrides as potential catalysts for CO2 hydrogenation. The potential of high energy resolution X‐ray absorption near‐edge structure (HERFD‐XANES) and valence‐to‐core X‐ray emission (VtC‐XES) is demonstrated with measurement on Stryker's reagent (Cu6H6) and [Cu3(μ3‐H)(dpmppe)2](PF6)2 (Cu3H), alongside a non‐hydride copper compound (Cu‐I). The XANES analysis reveals that coordination geometries strongly influence the spectra, providing only indirect details about hydride coordination. The VtC‐XES analysis exhibits a distinct signal around 8975 eV, offering a diagnostic tool to identify hydride ligands. Theoretical calculations support and extend these findings by comparing hydride‐containing complexes with their hydride‐free counterparts.

Erklärvideos. Praxis Deutsch 304.

Liveness-Norm in der Musikpädagogik – warum die Orientierung an Live-Musik kulturelle Vielfalt und Digitalisierung verhindert - Godau, Marc; Gosmann, Phillip (Seminar)

Digital participation of brain tumour patients in the assessment and treatment of communication disorders - Weiss Lucas, Carolin; Kochs, Sophia; Jost, Johanna; Loução, Ricardo; Kocher, Martin; Goldbrunner, Roland; Wiewrodt, Dorothee; Jonas, Kristina (Frontiers in Psychology)
Introduction Communication deficits have a severe impact on our social interactions and health-related quality of life. Subtle communication deficits are frequently overlooked or neglected in brain tumour patients, due to insufficient diagnostics. Digital tools may represent a valuable adjunct to the conventional assessment or therapy setting but might not be readily suitable for every patient. Methods This article summarises results of three surveys on the readiness for telemedicine among (a) patients diagnosed with high-grade glioma, (b) matched controls, and (c) speech and language therapists. The respective surveys assessed the motivation for participation in telemedical assessments and supposed influencing factors, and the use potential of digital assessment and therapy technologies in daily routine, with a spotlight on brain tumour patients and the future prospects of respective telemedical interventions. Respondents included 56 high-grade glioma patients (age median: 59 years; 48% males), 73 propensity-score matched neurologically healthy controls who were instructed to imagine themselves with a severe disease, and 23 speech and language therapists (61% <35 years; all females). Results and discussion The vast majority of the interviewed high-grade glioma (HGG) patients was open to digitisation, felt well-equipped and sufficiently skilled. The factorial analysis showed that digital offers would be of particular interest for patients in reduced general health condition ( p = 0.03) and those who live far from specialised treatment services ( p = 0.03). The particular motivation of these subgroups seemed to outweigh the effects of age, equipment and internet skills, which were only significant in the control cohort. The therapists' survey demonstrated a broad consensus on the need for improving the therapy access of brain tumour patients (64%) and strengthening their respective digital participation (78%), although digitisation seems to have yet hardly entered the therapists' daily practise. In summary, the combined results of the surveys call for a joint effort to enhance the prerequisites for digital participation of patients with neurogenic communication disorders, particularly in the context of heavily burdened HGG patients with limited mobility.

„Ich find’s aber trotzdem unfair.“. Argumentausbau in argumentativen Gesprächen und Briefen von Schüler*innen - Rezat, Sara; Grundler, Elke; Schmölzer-Eibinger, Sabine (Textprozeduren in Spannungsfeldern)

Erklärvideos. Basisartikel - Rezat, Sara; Feilke, Helmuth (Praxis Deutsch)

Textprozeduren in Spannungsfeldern

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Singen auf TikTok und Co. Sind Gesangspraktiken in (post)digitaler Kultur (k)ein Thema für die Musikpädagogik? - Godau, Marc (Stimme, Medien, Umwelt. Kinder- und Jugendstimme)

Modellierungen außerinstitutioneller Aneignungsprozesse digital-materieller Interfaces und (musik-)pädagogische Anschlüsse - Neuhausen, Timo; Ahlers, Michael (Musik – Digitalisierung – Bildung)

UNav-Sim: A Visually Realistic Underwater Robotics Simulator and Synthetic Data-Generation Framework - Amer, Abdelhakim; Álvarez-Tuñón, Olaya; Uğurlu, Halil İbrahim; Le Fevre Sejersen, Jonas; Brodskiy, Yury; Kayacan, Erdal (2023 21st International Conference on Advanced Robotics (ICAR))

TypeEvalPy: A Micro-benchmarking Framework for Python Type Inference Tools - Shivarpatna Venkatesh, Ashwin Prasad; Sabu, Samkutty; Wang, Jiawei; Mir, Amir M.; Li, Li; Bodden, Eric (Proceedings of the 46th International Conference on Software Engineering, Tool Demo Track)

Detecting Security-Relevant Methods using Multi-label Machine Learning - Johnson, Oshando; Piskachev, Goran; Krishnamurthy, Ranjith; Bodden, Eric (Proceedings of the 46th International Conference on Software Engineering, IDE Workshop)
To detect security vulnerabilities, static analysis tools need to be configured with security-relevant methods. Current approaches can automatically identify such methods using binary relevance machine learning approaches. However, they ignore dependencies among security-relevant methods, over-generalize and perform poorly in practice. Additionally, users have to nevertheless manually configure static analysis tools using the detected methods. Based on feedback from users and our observations, the excessive manual steps can often be tedious, error-prone and counter-intuitive. In this paper, we present Dev-Assist, an IntelliJ IDEA plugin that detects security-relevant methods using a multi-label machine learning approach that considers dependencies among labels. The plugin can automatically generate configurations for static analysis tools, run the static analysis, and show the results in IntelliJ IDEA. Our experiments reveal that Dev-Assist's machine learning approach has a higher F1-Measure than related approaches. Moreover, the plugin reduces and simplifies the manual effort required when configuring and using static analysis tools.

SootUp: A Redesign of the Soot Static Analysis Framework - Karakaya, Kadiray; Schott, Stefan; Klauke, Jonas; Bodden, Eric; Schmidt, Markus; Luo, Linghui; He, Dongjie (Tools and Algorithms for the Construction and Analysis of Systems)
Abstract Since its inception two decades ago, Soot has become one of the most widely used open-source static analysis frameworks. Over time it has been extended with the contributions of countless researchers. Yet, at the same time, the requirements for Soot have changed over the years and become increasingly at odds with some of the major design decisions that underlie it. In this work, we thus present SootUp , a complete reimplementation of Soot that seeks to fulfill these requirements with a novel design, while at the same time keeping elements that Soot users have grown accustomed to.

Symbol-Specific Sparsification of Interprocedural Distributive Environment Problems - Karakaya, Kadiray; Bodden, Eric (Proceedings of the IEEE/ACM 46th International Conference on Software Engineering)
Previous work has shown that one can often greatly speed up static analysis by computing data flows not for every edge in the program’s control-flow graph but instead only along definition-use chains. This yields a so-called sparse static analysis. Recent work on SparseDroid has shown that specifically taint analysis can be “sparsified” with extraordinary effectiveness because the taint state of one variable does not depend on those of others. This allows one to soundly omit more flow-function computations than in the general case. In this work, we now assess whether this result carries over to the more generic setting of so-called Interprocedural Distributive Environment (IDE) problems. Opposed to taint analysis, IDE comprises distributive problems with large or even infinitely broad domains, such as typestate analysis or linear constant propagation. Specifically, this paper presents Sparse IDE, a framework that realizes sparsification for any static analysis that fits the IDE framework. We implement Sparse IDE in SparseHeros, as an extension to the popular Heros IDE solver, and evaluate its performance on real-world Java libraries by comparing it to the baseline IDE algorithm. To this end, we design, implement and evaluate a linear constant propagation analysis client on top of SparseHeros. Our experiments show that, although IDE analyses can only be sparsified with respect to symbols and not (numeric) values, Sparse IDE can nonetheless yield significantly lower runtimes and often also memory consumptions compared to the original IDE.

On the repulsion effect of coupled Lamb wave modes - Nicolai, Marcel; Bulling, Jannis; Lugovtsova, Yevgeniya; Zeipert, Henning; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

Erinnerung als Formproblem. Feridun Zaimoglus Versuche, deutsche Geschichte ‚zu schreiben‘: „Führer“ (2021) und „Bewältigung“ (2022) - Eke, Norbert (Feridun Zaimoglu. Kasseler Grimm-Poetikprofessur 2023)

Zwischen Herrschaft und Utopie . Eine theologische Reflexion über die ambivalente Mensch-Tier-Beziehung - Herdramm, Henrike (Laudato)
Keywords: Tiertheologie; Tierethik; Psalm 104; Mensch-Tier-Beziehung

Schulleitungen als Promotoren. Unterstützung digitalisierungsbezogener Schulentwicklungsprozesse durch Schulleitungen und deren Wahrnehmung durch Lehrpersonen. - Gerick, Julia; Kieseler, Janine; Herrmann, Daniel; Eickelmann, Birgit (MedienPädagogik (Occasional Papers))

Evaluating Security Through Isolation and Defense in Depth - Bodden, Eric; Pottebaum, Jens; Fockel, Markus; Gräßler, Iris (IEEE Security & Privacy)
Keywords: Law; Electrical and Electronic Engineering; Computer Networks and Communications

Common pitfalls to avoid while using multiobjective optimization in machine learning - Akhter, Junaid; Fährmann, Paul David; Sonntag, Konstantin; Peitz, Sebastian (arXiv)

Beschreibung des akustischen Verhaltens verklebter plattenförmiger Strukturen mittels Kopplungsmodellen - Zeipert, Henning; Hölscher, Jonas; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

Métodos de la mediación de cultura en el entrenamiento práctico de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Revista Lengua y Cultura)
This study investigates the teaching methods that future teachers of German as a foreign language use in cultural mediation. Utilizing a qualitative and hermeneutic approach, it analyzes data from a teacher-training module of the International Master's in German as a Foreign/Second Language that Friedrich Schiller University Jena in Germany offers. Participants taught an online course to students from a Japanese university, which focused on cultural learning. Within the teacher training module, the participants discussed their lesson plans, conducted classes, and subsequently reflected on their teaching practices by exploring and critiquing the practical application of their teaching skills. The analysis, which was conducted using qualitative evaluative content analysis following Kuckartz's (2018) approach, revealed a preference for distributive/instructive methods, with some recognition of interactive and collaborative methods. A tendency towards both repetitive and reflective practices was evident, with a predominant focus on content that was specific to a supposed target culture rather than intercultural or transcultural content. The study highlights the need to balance knowledge transmission with the development of critical and reflective skills in cultural mediation. It emphasizes the importance of incorporating collaborative and interactive methods, which promote a critical attitude that is necessary in language teachers and learners. In conclusion, this study advocates adaptive and reflective teaching as an essential component in the training of future language teachers in globalized contexts.
Keywords: cultural mediation; teacher training; foreign language teaching; teaching methods; teaching practice

Developing a VR Factory Walkthrough for Use in Schools - Krings, Sarah Claudia; Yigitbas, Enes; Sauer, Stefan (Proceedings of the 10th International Working Conference on Human-Centered Software Engineering (HCSE'24))

Authenticité et patrimoine culturel. Genèse et adoption du critère d‘authenticité par la Convention du Patrimoine mondia - Seng, Eva- Maria (Nouvelles lectures patrimoniales. Le Pays de la Loire au miroir de l’Europe)

Die Leiden des jungen (Datenaus-) Werthers - Einblicke in die Praxis der empirischen Rechtsforschung - Bartlitz, David (Rechtstatsachen im Privatrecht)

Rechtstatsachen im Privatrecht

Untersuchung piezoelektrischer Materialeigenschaften unter hydrostatischer Last - Friesen, Olga; Pasha, Muhammad Ahsan; Schwengelbeck, Max; Claes, Leander; Baumhögger, Elmar; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)
Piezoelektrische Keramiken finden sowohl in Sensoren als auch in Aktoren Anwendung. Bei Hochleistungs-Ultraschallanwendungen sind diese Komponenten erheblichen elektrischen und mechanischen Belastungen ausgesetzt, was zum Auftreten nichtlinearer Effekte führt. Um das nichtlineare Materialverhalten piezoelektrischer Keramiken zu charakterisieren, kann eine statische mechanische Last aufgebracht werden, die den mechanischen Arbeitspunkt verschiebt. Durch Variation dieser statischen mechanischen Belastung kann das lineare Verhalten in jedem Betriebspunkt charakterisiert werden, woraufhin die nichtlinearen Eigenschaften des Materials angenähert werden können. Allerdings ist die Sicherstellung einer homogenen mechanischen Last anspruchsvoll. Alternativ kann eine hydrostatische Belastung realisiert werden, indem die Probe in einen Behälter gegeben wird, der mit unter Druck stehendem Fluid gefüllt ist. Dadurch wird eine gleichmäßige Lastverteilung über die Oberfläche der Probe erreicht. In diesem Beitrag wird ein Versuchsaufbau zur Durchführung elektrischer Impedanzmessungen an piezoelektrischen Keramiken in einem Druckbehälter vorgestellt. Die Probe wird im Inneren des Druckbehälters elektrisch kontaktiert. Unter Verwendung von unter Druck stehendem Argon wird auf diese Weise die Messung der elektrischen Impedanz unter hydrostatischer Last von bis zu 200 bar ermöglicht. Anschließend wird ein inverses Verfahren angewendet, um die Materialparameter in Abhängigkeit von der aufgebrachten Last zu ermitteln.

Einfluss der periodischen Struktur auf geführte Wellen in gewebeverstärkten Polymeren - Claes, Leander (Fortschritte der Akustik - DAGA 2024)

Inverses Verfahren zur Identifikation piezoelektrischer Materialparameter unterstützt durch neuronale Netze - Koch, Kevin; Claes, Leander; Jurgelucks, Benjamin; Meihost, Lars; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

Effects of Human Avatar Representation in Virtual Reality on Inter-Brain Connections - Yigitbas, Enes; Kaltschmidt, Christian (Proceedings of the 8th International Conference on Artificial Intelligence and Virtual Reality (AIVR’24))

An Exploratory Study of Fear-Inducing Factors in Virtual Reality Experiences - Leichtweiß, Justus; Yigitbas, Enes (Proceedings of the 12th International Conference on Serious Games and Applications for Health (SeGAH'24))

Interaction Techniques for Remote Maintenance in an AR Shared Environment - Krings, Sarah Claudia; Biermeier, Kai; Yigitbas, Enes (Proceedings of the 10th International Working Conference on Human-Centered Software Engineering (HCSE'24))

Prototyping Cross-Reality Escape Rooms - Krois, Sebastian; Yigitbas, Enes (Proceedings of the 10th International Working Conference on Human-Centered Software Engineering (HCSE'24))